2022
DOI: 10.3389/fenvs.2022.878060
|View full text |Cite
|
Sign up to set email alerts
|

How Does Green Credit Promote Carbon Reduction? A Mediated Model

Abstract: Using China’s provincial panel data from 2006 to 2016, this paper develops a dynamic panel data model to investigate the impact and mechanism of green credit on carbon emissions at the national and regional levels. According to the findings, green credit significantly reduces carbon emissions, with the eastern region having the greatest reduction effect. Green credit, with the exception of the western region, has a strong positive impact on disruptive low-carbon innovation. When green credit is combined with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Jiang et al (2020) used a dynamic panel data model to empirically examine the effects of green credits on carbon emissions and found that green credits have a significant inhibitory effect on carbon emissions. In terms of the mechanism, green credit can indirectly suppress carbon emissions through two paths: promoting technological innovation (Lyu et al, 2022) and optimizing industrial structure (Hu and Zheng, 2022). Additionally, Qin and Cao (2022) used a DID model to evaluate the carbon reduction effects of green credit policies and showed that green credit could also reduce carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al (2020) used a dynamic panel data model to empirically examine the effects of green credits on carbon emissions and found that green credits have a significant inhibitory effect on carbon emissions. In terms of the mechanism, green credit can indirectly suppress carbon emissions through two paths: promoting technological innovation (Lyu et al, 2022) and optimizing industrial structure (Hu and Zheng, 2022). Additionally, Qin and Cao (2022) used a DID model to evaluate the carbon reduction effects of green credit policies and showed that green credit could also reduce carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jiang et al (2020) empirically studied the relationship between green credit on carbon emissions and found that green credit has a significant negative effect on carbon emissions. In terms of the mechanism, green credit mainly indirectly restrains carbon emissions by promoting technological innovation (Lyu et al, 2022) and optimizing industrial structure (Hu and Zheng, 2022). However, few studies have explored the agricultural carbon emission reduction effect of green credit.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al found that green credit helped to enhance the effectiveness of China’s green economy, and positively contributed to regional economic growth [ 18 , 19 , 20 ], and this promotion also had spatial spillover effects [ 21 ]. The implementation of green credit policies helped to reduce pollutant emissions at both the national level and at the level of heavily polluting industries [ 22 , 23 ], reducing carbon and sulfur dioxide emissions and curbing PM2.5 concentrations [ 24 , 25 , 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Liu et al (2021) studied the relationship between green credit policy and enterprises' green technology innovation performance. Lyu et al (2022) explored the impact and mechanism of green credit policy on carbon emissions at the national and regional levels. Lai et al (2022) discussed the impact of green credit on new energy enterprises' value.…”
Section: Green Creditmentioning
confidence: 99%